Research on situated motivation and emotion: Progress and open problems. (October 2022) - Pekrun, Reinhard; Marsh, Herbert W.
Abstract: Research on situated motivation and emotion in education has made substantial progress, as documented in the contributions to this special issue. We discuss how this field can make further headway. First, we address the ambiguous meaning of the term situation and propose a 2 × 2 model of situational variation across time and context. From this model, it follows that we should consider study designs that address not only variation over time and single settings, but also across broader socio-cultural contexts. We then explain the need to overcome the current fragmentation of theoretical models by integrating constructs and theoretical propositions. Next, we discuss strategies to improve methodology, including further development of empirical paradigms, analyzing the equivalence of effects across levels and persons, and use of dynamic modeling of data from different sources. Finally, we argue that we need to broaden research perspectives by developing formalized micro- and macro-theories; considering motivation and emotion beyond the achievement domain; including samples from non-WEIRD countries; and investigating the generalizability of principles and practices across persons, cultural contexts, and historical times.